Enterobius vermicularis salpingitis seen in the setting of ectopic pregnancy in a Malaysian patient: A case report - Ngui, R.; Ravindran, S.; Ong, D.B.L.; Chow, T.K.; Low, K.P.; Nureena, Z.S.; Rajoo, Y.; Chin, Y.T.; Amir, A.; Ahmad, A.F.; Lim, Y.A.L.; Mahmud, R. (American Society for Microbiology, 2014)
We report a rare and unusual case of invasive Enterobius vermicularis infection in a fallopian tube. The patient is a 23-year-old woman from Malaysia who presented with suprapubic pain and vaginal bleeding. A clinical diagnosis of ruptured right ovarian ectopic pregnancy was made. She underwent a laparotomy with a right salpingo-oophorectomy. Histopathological examination of the right fallopian tube showed eggs and adult remnants of E. vermicularis and was confirmed using PCR and DNA sequencing.